Benzenesulfonamides act as open-channel blockers on K V 3.1 potassium channel - Bassetto Junior, Carlos Alberto Zanutto [UNESP] (2019)
K V 3.1 blockers can serve as modulators of the rate of action potential firing in neurons with high rates of firing such as those of the auditory system. We studied the effects of several bioisosteres of N-alkylbenzenesulfonamides, and molecules derived from sulfanilic acid on K V 3.1 channels, heterologously expressed in L-929 cells, using the whole-cell patch-clamp technique. Only the N-alkyl-benzenesulfonamides acted as open-channel blockers on K V 3.1, while molecules analogous to PABA (p-aminobenzoic acid) and derived from sulfanilic acids did not block the channel. The IC 50 of six N-alkyl-benzenesulfonamides ranged from 9 to 55 µM; and the Hill coefficient suggests the binding of two molecules to block K V 3.1. Also, the effects of all molecules on K V 3.1 were fully reversible. We look for similar features amongst the molecules that effectively blocked the channel and used them to model a blocker prototype. We found that bulkier groups and amino-lactams decreased the effectiveness of the blockage, while the presence of NO 2 increased the effectiveness of the blockage. Thus, we propose N-alkylbenzenesulfonamides as a new class of K V 3.1 channel blockers.